Establishment and serial passage of cell cultures derived from LuCaP xenografts. Issue 12 (6th June 2013) - Young, Sarah R.; Saar, Matthias; Santos, Jennifer; Nguyen, Holly M.; Vessella, Robert L.; Peehl, Donna M.
Abstract: BACKGROUND: LuCaP serially transplantable xenografts derived from primary and metastatic human prostate cancer encompass the molecular and cellular heterogeneity of the disease and are an invaluable resource for in vivo preclinical studies. A limitation of this model, however, has been the inability to establish and passage cell cultures derived from the xenografts. Here, we describe a novel spheroid culture system that supports long‐term growth of LuCaP cells in vitro. METHODS: Xenografts were minced and digested with collagenase. Tissue dissociation was terminated while the majority of cells remained as clusters rather than single cells. The cell clusters were suspended in StemPro medium supplemented with R1881 and Y‐27632, a Rho kinase inhibitor, and placed in ultralow attachment dishes for spheroid culture. Serial passage was achieved by partial digestion to small clusters with trypsin/EDTA in the presence of Y‐27632. Cell viability, growth and phenotype were monitored with LIVE/DEAD®, MTS, qRT‐PCR, and immunocytochemical assays. RESULTS: Cells from six LuCaP xenografts formed proliferating spheroids that were serially passaged a minimum of three times and cryopreserved. Two of the cell lines, LuCaP 136 and LuCaP 147, were further passaged and characterized. Both expressed biomarkers characteristic of the xenografts of origin, were determined to be of independent origin by STR fingerprinting, and were free of mycoplasma. LuCaP 147 formed tumors similar to the original xenograft when injected into mice. CONCLUSIONS: The ability to culture LuCaP cells affords new opportunities for fast, cheap, and efficient preclinical studies and extends the value of the LuCaP xenograft models. Prostate 73:1251–1262, 2013 . © 2013 Wiley Periodicals, Inc.